THE AESTHETICS OF AGUS LEONARDUS’ POSTCARD PHOTOGRAPHY ON YOGYAKARTA SOCIO-CULTURAL ACTIVITIES - Yuniar, Anang Ma'ruf Bagus; Prasetyo, Andry (Seni Media Rekam ISI Surakarta, 2023)
This text aims to assess the aesthetic value of Agus Leonardus' Yogyakarta social and cultural activities-themed postcard photography works from both ideational and technical perspectives. This research adopts a qualitative interpretative approach, describing the postcard photo works as data. The analysis utilizes Soedjono's aesthetic theory, which encompasses both technical and ideational aspects. The results of this study indicate that Agus Leonardus' photos ideationally highlight ideas and themes related to social and cultural activities in Yogyakarta. On a technical level, they demonstrate a skillful combination of various visual elements, such as lines, shapes, and lighting. The arrangement of these visual elements in Leonardus' works is carefully considered, ensuring that each photo complements and supports one another, thereby enhancing the aesthetic value of the overall collection.